Problems In The Evaluation Of Islamic Education Policy Studies - Fawait Syaiful Rahman (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2022)
Islamic educational institutions such as madrasahs and islamic boarding schools have succeeded in building a human disposition with a religious culture that loves the Republic of Indonesia. Even so, there is still a skewed view of the informal institution. According to the assessment of some people, the output or autcame of madrasah institutions and islamic boarding schools is less noticed by the job market. This skewed view is refuted through the existence of madrasas and islamic boarding schools which are increasingly believed to give birth to Muslim scholars. The method used is descriptive qualitative. While the approach used is literature. The results of the analysis get the following findings, the Islamic Education policy from time to time experiences quite heavy dynamics. Islamic education in the Dutch era was subjected to acts of policy discrimination. Islamic education only got a breath of fresh air after the dutch leadership fell to the Japanese. The journey of Islamic education can be said to have truly become independent after Indonesia became independent. There are five problems in the effort to evaluate the study of Islamic Education in Indonesia, including limited government power, disagreements with a problem, subjectivity in interpretation, limitations in resource management research, and complexity of human behavior.